Born Both Ways: The Alloparenting Hypothesis for Sexual Fluidity in Women - Barry X. Kuhle; Sarah Radtke (Evolutionary Psychology, 2013)
Given the primacy of reproduction, same-sex sexual behavior poses an evolutionary puzzle. Why would selection fashion motivational mechanisms to engage in sexual behaviors with members of the same sex? We propose the alloparenting hypothesis, which posits that sexual fluidity in women is a contingent adaptation that increased ancestral women's ability to form pair bonds with female alloparents who helped them rear children to reproductive age. Ancestral women recurrently faced the adaptive problems of securing resources and care for their offspring, but were frequently confronted with either a dearth of paternal resources due to their mates' death, an absence of paternal investment due to rape, or a divestment of paternal resources due to their mates' extra-pair mating efforts. A fluid sexuality would have helped ancestral women secure resources and care for their offspring by promoting the acquisition of allomothering investment from unrelated women. Under this view, most heterosexual women are born with the capacity to form romantic bonds with both sexes. Sexual fluidity is a conditional reproductive strategy with pursuit of men as the default strategy and same-sex sexual responsiveness triggered when inadequate paternal investment occurs or when women with alloparenting capabilities are encountered. Discussion focuses on (a) evidence for alloparenting and sexual fluidity in humans and other primates; (b) alternative explanations for sexual fluidity in women; and (c) fourteen circumstances predicted to promote same-sex sexual behavior in women.